Evodiamine suppresses endometriosis development induced by early EBV exposure through inhibition of ERβ - Wang, Junling; Liang, Yuanqi; Liang, Xiaoru; Peng, Huijuan; Wang, Yongxia; Xu, Mingtao; Liang, Xuefang; Yao, Helen; Liu, Xiaohan; Zeng, Liqin; Yao, Paul; Xiang, Dongfang (Frontiers in Pharmacology, 2024)
Introduction: Endometriosis (EMS) is characterized as a prevalent gynecological inflammatory disorder marked by the existence of endometrial tissues situated beyond the uterus. This condition leads to persistent pelvic pain and may contribute to infertility. In this investigation, we explored the potential mechanism underlying the development of endometriosis (EMS) triggered by transient exposure to either latent membrane protein 1 (LMP1) or Epstein-Barr virus (EBV) in a mouse model. Additionally, we examined the potential inhibitory effect of evodiamine (EDM) on EMS. Methods: Immortalized human endometrial stromal cells (HESC) or epithelial cells (HEEC) were transiently exposed to either EBV or LMP1. The presence of evodiamine (EDM) was assessed for its impact on estrogen receptor β (ERβ) expression, as well as on cell metabolism parameters such as redox balance, mitochondrial function, inflammation, and proliferation. Additionally, a mixture of LMP1-treated HESC and HEEC was administered intraperitoneally to generate an EMS mouse model. Different dosages of EDM were employed for treatment to evaluate its potential suppressive effect on EMS development. Results: Transient exposure to either EBV or LMP1 triggers persistent ERβ expression through epigenetic modifications, subsequently modulating related cell metabolism for EMS development. Furthermore, 4.0 µM of EDM can efficiently reverse this effect in in vitro cell culture studies. Additionally, 20 mg/kg body weight of EDM treatment can partly suppress EMS development in the in vivo EMS mouse model. Conclusion: Transient EBV/LMP1 exposure triggers permanent ERβ expression, favoring later EMS development, EDM inhibits EMS development through ERβ suppression. This presents a novel mechanism for the development of endometriosis (EMS) in adulthood stemming from early Epstein-Barr virus (EBV) exposure during childhood. Moreover, evodiamine (EDM) stands out as a prospective candidate for treating EMS.